Path Loss Model with Antenna Height Dependency under Indoor Stair Environment. (22nd July 2014) - Yu, Yu; Liu, Yang; Lu, Wen-Jun; Zhu, Hong-Bo
Abstract : A novel, receiving antenna-height-dependent path loss model under indoor stair environment is presented. The effect of a cross-beam in the stairs is also considered. The proposed model can be applied to describe both of the line-of-sight (LOS) and the non-LOS (NLOS) cases. By using least square criterion, the parameters of proposed model are extracted. Finally, using the maximum likelihood estimation, the precision of the proposed model is evaluated by the standard deviation of shadowing.